Life Skill Activities To Increase The Independence Of Early Childhood - Widya Fiamita; Hadiqotul Luluk; Hena Dian Ayu (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
This Systematic Literature Review (SLR) explores the impact of life skill activities on increasing independence in early childhood. The review aims to synthesize current research findings to answer three main questions: (1) Do life skill activities significantly enhance independence among young children? (2) Who are the key stakeholders involved in implementing life skill activities? (3) What are the challenges in implementing life skill activities in early childhood education? The SLR was conducted by systematically searching five major databases-Scopus, ScienceDirect, Wiley, JSTOR, and Mendeley-using relevant keywords. Inclusion criteria focused on peer-reviewed articles from the last ten years, involving children aged 5-6 years in both formal and non-formal early childhood education settings. After a rigorous screening process, ten studies were included for thematic analysis. The findings indicate that well-designed life skill activities play a significant role in fostering independence in early childhood, particularly in areas such as self-care, decision-making, and social-emotional skills. The review also highlights the importance of collaboration between teachers and parents in supporting these activities. However, gaps remain in terms of standardized implementation methods and limited parental involvement. In conclusion, life skill activities are essential for developing independence in early childhood, but further research and practical guidelines are needed to optimize their implementation in diverse educational contexts.